Improving Resolution In NMR In The Presence of Microcarriers Using Holmium-DOTA - Hasselberg,Fredrik; Laurell,Niklas (2024)
This research is part of a larger project exploring the use of surface modified microcarriers, specifically polystyrene and PDMS, as a chromatographic medium to enable high resolution liquid state NMR-analysis of biological samples such as blood and plasma. The purpose of the microcarriers is to bind proteins and lipids, which distorts the NMR-spectrum, hence enabling identification of metabolites. This would enable for direct NMR-analysis of biological samples which would reduce procedure complexity, operation duration from several hours to a couple of minutes and finally usage and waste of organic solvents. The primary objective is to determine whether adding a paramagnetic solvent to a suspension of water and microcarriers can achieve high resolution NMR-peaks, through so called magnetic homogeneity. Experiments were conducted at the Biomedical Center, Lund University, where a NMR tube was filled with a microcarrier-water suspension and small amounts of fumarate, used to measure NMR peak linewidth, as a measure of resolution. To achieve homogeneity a solution of holmium DOTA, Ho-DOTA, was incrementally added to the tube. After each addition, the sample was mixed thoroughly and NMR analysis was performed to measure linewidth changes. The results suggest that adding Ho-DOTA can significantly enhance magnetic homogeneity and NMR resolution. In the PDMS suspension a minimum linewidth of 22Hz was obtained in proton-NMR and 8Hz in 13C NMR spectroscopy. This finding holds potential for streamlining the analysis of complex biological samples, reducing the time and complexity involved in traditional NMR preparation methods. However, in the polystyrene solution line broadening was only achieved. Althought, this results suggest that our method might also be used to measure the magnetic susceptibility of an unknown material.